2016
DOI: 10.1590/0004-282x20160072
|View full text |Cite
|
Sign up to set email alerts
|

Currents issues in cardiorespiratory care of patients with post-polio syndrome

Abstract: Post-polio syndrome (PPS) is a condition that affects polio survivors years after recovery from an initial acute attack of the poliomyelitis virus. Most often, polio survivors experience a gradual new weakening in muscles that were previously affected by the polio infection. The actual incidence of cardiovascular diseases (CVDs) in individuals suffering from PPS is not known. However, there is a reason to suspect that individuals with PPS might be at increased risk. Method A search for papers was made in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(43 reference statements)
0
7
0
1
Order By: Relevance
“…The most commonly used instruments to assess non-motor domains include the Fatigue Severity Scale (FSS) (116), Fatigue Impact Scale (FIS), Piper Fatigue Scale (PFS), Short Fatigue Questionnaire (SFQ), Nottingham Health Profile (NHP), Physical activity scale for the elderly (PASE) (117), Polio Problem List (PPL), Visual analog scale (VAS) (118), Multidimensional Fatigue Inventory (MFI-20) (119), World Health Organization quality of life abbreviated scale (WHOQOL-BREF) (120), University of Washington Self-Efficacy Scale (UW-SES) (121), Sickness Impact Profile (SIP), 36-item Short Form Health Survey (SF-36) (112). Sleep disturbances (97) and respiratory function can be formally assessed through polysomnography and pulmonary function tests (PFT) (122, 123). RLS is typically diagnosed clinically (124) and most commonly evaluated using the validated international RLS rating scale (IRLS) (87, 93, 125).…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used instruments to assess non-motor domains include the Fatigue Severity Scale (FSS) (116), Fatigue Impact Scale (FIS), Piper Fatigue Scale (PFS), Short Fatigue Questionnaire (SFQ), Nottingham Health Profile (NHP), Physical activity scale for the elderly (PASE) (117), Polio Problem List (PPL), Visual analog scale (VAS) (118), Multidimensional Fatigue Inventory (MFI-20) (119), World Health Organization quality of life abbreviated scale (WHOQOL-BREF) (120), University of Washington Self-Efficacy Scale (UW-SES) (121), Sickness Impact Profile (SIP), 36-item Short Form Health Survey (SF-36) (112). Sleep disturbances (97) and respiratory function can be formally assessed through polysomnography and pulmonary function tests (PFT) (122, 123). RLS is typically diagnosed clinically (124) and most commonly evaluated using the validated international RLS rating scale (IRLS) (87, 93, 125).…”
Section: Resultsmentioning
confidence: 99%
“…This is a justifiable fact since we are recruiting already staggering neuromuscular units as a result of PAA and that the new skeletal muscle weakness in PPS can be triggered by disuse, over training or by a combination of both. On the other hand other studies have demonstrated that the regular practice of exercise in patients with SPP can increase muscular endurance, besides bringing benefits to the cardiovascular system [5,7]. In an elegant review carried out by Tiffreau et al, 14 works related to physical exercise in SPP were selected, two of which involved exclusively aerobic training, seven on resistance training, two on hydrotherapy, one on concurrent training (aerobic and resisted in the same therapeutic session) and one where exercise prescription was performed according to subjects' daily observation.…”
Section: Opinionmentioning
confidence: 98%
“…Physical rehabilitation in patients with PPS can be compounded by performing resistance exercises (strength training), aerobic exercises, stretching exercises, energy conservation techniques and when necessary the prescription of orthoses [3][4][5][6].…”
Section: Opinionmentioning
confidence: 99%
“…The integrity of these neurons is compromised after many years of use by the persistent metabolic stress, which eventually results in motor unit wasting, creating gaps in the neuromuscular junction, and this is regarded as the main cause of fatigue. [27]…”
Section: Clinical Manifestationsmentioning
confidence: 99%